1971
DOI: 10.3181/00379727-138-35994
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Furazolidone in Swine

Abstract: Studies in rats, dogs, chickens, and rabbits (1-5) show the rapid conversion of ingested nitrofurans to a limited number of structurally related metabolic products, not all of which have been positively identified. However, from work with isotopically labeled nitrofurans, (6) i t is apparent that a consider-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

1972
1972
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…The intensely yellow-colored, polar me tabolites of furazolidone and nitrofurazone which have previously been isolated from the urine of swine [9], rabbits and other spe cies [10], respectively, have been positively identified in this paper as 4-hydroxyfurazolidone and 4-hydroxynitrofurazone. Further more, we have confirmed that 4-hydroxynitrofurantoin is excreted in the urine of rats which have been dosed with nitrofurantoin [3,4], The earlier paper by Olivard et al [3] did not, however, describe the species of rat used, the conditions under which the nitro furantoin was administered or if any pre- derivative (a, c, e) and the rat urinary metabolite (b, d, f) were isolated, purified and spectra generated as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 68%
“…The intensely yellow-colored, polar me tabolites of furazolidone and nitrofurazone which have previously been isolated from the urine of swine [9], rabbits and other spe cies [10], respectively, have been positively identified in this paper as 4-hydroxyfurazolidone and 4-hydroxynitrofurazone. Further more, we have confirmed that 4-hydroxynitrofurantoin is excreted in the urine of rats which have been dosed with nitrofurantoin [3,4], The earlier paper by Olivard et al [3] did not, however, describe the species of rat used, the conditions under which the nitro furantoin was administered or if any pre- derivative (a, c, e) and the rat urinary metabolite (b, d, f) were isolated, purified and spectra generated as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 68%
“…Furaltadone (pKa 5.0) was strongly related to urine flow (passive drug reabsorption), which effect is less pronounced (P<0.1) for nitrofurazone. For nitrofurans the metabolism is poorly understood and numerous metabolites are postulated (2,5,10,11,13). Two main biotransformation pathways may affect nitrofurans: in the side chain (R) and the nitrofuran ring itself (indicated as A and B, respectively, in the basic molecular nitrofuran structure, Fig.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Based on our data for furaltadone and nitrofurazone a withdrawal time of at least 3 to 5 days is required for calves if there is no accumulation of the parent drug in the edible tissues, which is unlikely (6,8,10,11,13). However, analogously to furazolidone administered orally to pigs, a longer persistence of metabolites compared with the parent drug may occur in edible tissues of calves (11,13). Recently it was shown, in piglets, that fourteen days after cessation of oral furazolidone administration, residues equivalent to 2 ppm of the parent drug were still detected in muscle (13).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Reference has been made to carcinogenicity in mice and rats after long-term administration (Ali, 1983) and to high mutagenic activity employing Salmonella (McCalla and Voutsinos, 1974). In view of these toxic effects, the possibility of residues of the drug or its metabolites in meat for human consumption is a major concern.Studies using 14C-labeled furazolidone in swine have indicated that the main excretion pathway for this drug is the urine (Vroomen et al, 1986b;Tennent and Ray, 1971). The half-life appears to be 2.6 h after a single dose, but radioactivity can still be detected in muscle tissue after 14 days.…”
mentioning
confidence: 99%
“…Studies using 14C-labeled furazolidone in swine have indicated that the main excretion pathway for this drug is the urine (Vroomen et al, 1986b;Tennent and Ray, 1971). The half-life appears to be 2.6 h after a single dose, but radioactivity can still be detected in muscle tissue after 14 days.…”
mentioning
confidence: 99%